2008
DOI: 10.1099/ijs.0.65724-0
|View full text |Cite
|
Sign up to set email alerts
|

Marinomonas basaltis sp. nov., a marine bacterium isolated from black sand

Abstract: A Gram-negative, aerobic, slightly halophilic, rod-shaped bacterium was isolated from black sand in Soesoggak, Jeju island, Korea. The strain, designated J63 T , was oxidase-and catalase-positive and arginine dihydrolase-negative. The isolate required Na + for growth and differed from phenotypically related species by being able to utilize sucrose and D-galactose as a carbon source. Phylogenetic analysis based on the sequence of the 16S rRNA gene revealed that strain J63 T belongs to the genus Marinomonas. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…The phenotypic features of M. basaltis LMG 25279 T and M. communis LMG 2864 T were very similar, except for some features, namely that M. communis LMG 2864 T utilized sucrose, d -fructose, succinamic acid, urocanic acid and putrescine and had urease activity, whereas M. basaltis LMG 25279 T did not. Some phenotypic results for M. basaltis LMG 25279 T obtained in this study conflict with those reported by Chang et al (2008). They reported no growth in less than 1 % or more than 7 % NaCl and no esterase (C4), esterase lipase (C8) or naphthol-AS-BI-phosphohydrolase activities, but activities for trypsin and N -acetyl-β-glucosaminidase were present, and assimilation of l -arabinose, l -aspartic acid and glycerol.…”
contrasting
confidence: 96%
See 2 more Smart Citations
“…The phenotypic features of M. basaltis LMG 25279 T and M. communis LMG 2864 T were very similar, except for some features, namely that M. communis LMG 2864 T utilized sucrose, d -fructose, succinamic acid, urocanic acid and putrescine and had urease activity, whereas M. basaltis LMG 25279 T did not. Some phenotypic results for M. basaltis LMG 25279 T obtained in this study conflict with those reported by Chang et al (2008). They reported no growth in less than 1 % or more than 7 % NaCl and no esterase (C4), esterase lipase (C8) or naphthol-AS-BI-phosphohydrolase activities, but activities for trypsin and N -acetyl-β-glucosaminidase were present, and assimilation of l -arabinose, l -aspartic acid and glycerol.…”
contrasting
confidence: 96%
“…DDH between M. basaltis LMG 25279 T and M. communis LMG 2864 T was above 70 % (78 %), which suggests that these species are synonymous. Chang et al (2008) obtained 56.2 % DDH between the same pair of type strains, but additional data from the present study (see below) support our value of 78 %. The authenticity of M. basaltis LMG 25279 T and M. communis LMG 2864 T used in this study was verified by 16S rRNA gene sequencing.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The number of species in this genus has increased during recent years, after the initial description of the genus by Van Landschoot & De Ley (1983). At the time of writing, the list of species with validly published names in the genus Marinomonas included M. communis and M. vaga (formerly Alteromonas communis and A. vaga ; Van Landschoot & De Ley, 1983; Baumann et al , 1972), M. mediterranea (Solano & Sanchez-Amat, 1999), M. primoryensis (Romanenko et al , 2003), M. pontica (Ivanova et al , 2005), M. dokdonensis (Yoon et al , 2005), M. aquimarina (Macián et al , 2005), M. ushuaiensis (Prabagaran et al , 2005), M. polaris (Gupta et al , 2006), M. ostreistagni (Lau et al , 2006), M. arctica (Zhang et al , 2008), M. basaltis (Chang et al , 2008), M. arenicola (Romanenko et al , 2009), M. balearica and M. pollencensis (Espinosa et al , 2010). M. brasilensis has since been added to the genus and M. communis and M. basaltis have been recognized as heterotypic synonyms (Chimetto et al ., 2011).…”
mentioning
confidence: 99%
“…The DNA G+C content is 41–50 mol%. The genus Marinomonas belongs to the class Gammaproteobacteria , and it includes 22 species with validly published names at the time of writing, reported from various marine habitats: seawater from the Mediterranean Sea (Solano & Sanchez-Amat, 1999), subantarctic regions (Gupta et al , 2006; Prabagaran et al , 2005), the Black Sea (Ivanova et al , 2005), the East Sea of Korea (Yoon et al , 2005) and a pearl-oyster culture pond (Lau et al , 2006), coastal sea-ice of the Sea of Japan (Romanenko et al , 2003), the seagrass Posidonia oceanica (Espinosa et al , 2010), the coral Mussismilia hispida (Chimetto et al , 2009), oysters and seawater (Macián et al , 2005), marine sediment (Romanenko et al , 2009) and black sand (Chang et al , 2008).…”
mentioning
confidence: 99%